Exploring the localization effects of organ system-based curriculum: a comparative study of different teaching programs in medical education - Zhang, Huiqun; Li, Jiaying; Zhong, Lujie; Zheng, Jianmin; Chen, Xiaoyun; Wen, Shenyu; Li, Yun; Li, Jianhua (Frontiers in Education, 2025)
BackgroundOrgan system-based curriculum (OSBC) has been introduced to improve traditional discipline-based teaching in Chinese medical schools. This study evaluates the localization effects of OSBC by comparing short term, i.e., final exam, objective structured clinical examination (OSCE) and long term i.e., national medical licensing examination (NMLE) outcomes across different teaching classes. Findings aim to inform future curriculum reform and faculty development in localized medical education.MethodsThis study employed a quasi-experimental design and obtained 111 undergraduate medical students through cluster sampling. Medical students were grouped by teaching schemes, gender and grade with short-term outcomes assessed via final exams and OSCE, and long-term outcomes via post-graduation NMLE scores.ResultsThe results of Wilcoxon rank sum test showed that the OSCE scores of students in Nanshan class were higher than those in traditional teaching class, especially in the modules of Medical History Collection and Physical Examination (Z = 1.979, p = 0.048; Z = 2.405, p = 0.016). Yet, the comparison of NMLE items revealed no significant differences between the two student groups. Males and earlier cohorts exhibited slight advantages in OSCE/NMLE, though non-significant.ConclusionThe localized OSBC demonstrates early prospects in clinical skills highlighting the need for optimized resource allocation personalized guidance and holistic student development in medical education reform, offering insights for the exchange and practice of international medical education.